Ultralight aircraft and conventional digital cameras as an alternative for urban mapping - Román Edén Parra-Galaviz; Manuel de Jesús Pérez-Valdez; Omar Llanes-Cárdenas; Lennin Enrique Amador-Castro; Rafael Macías-Segura; Ciro de la Concepción Díaz-Hernández; Alberto Gaxiola (Transportation Research Interdisciplinary Perspectives)
Mapping plays a crucial role in urban planning by assisting authorities in making informed decisions regarding city growth and infrastructure placement. Unmanned Aerial Vehicles (UAVs) are employed extensively for this purpose, owing to their ease of operation and advanced georeferencing capabilities facilitated by integrated cameras coupled with Global Navigation Satellite System (GNSS) devices. However, some drawbacks have been identified, such as limited battery life, strict airspace regulations, and difficulties in mapping extensive territories due to the need for numerous takeoffs. Also, planes adapted with photogrammetric cameras are costly and bulky. On the other hand, Ultralight aircraft (ULAC) and Conventional Digital Cameras (CDC) are accessible devices. In this sense, this research explores ULACs coupled with CDCs as a low-cost alternative. A 70 km2 city was mapped using a conventional 39-megapixel camera mounted on a ULAC at 1000 m altitude to validate these tools. Digital processing yielded a ground resolution of 19.7 cm/pixel and root mean square errors (RMSE) of 32 cm in planimetry and 25 cm in altimetry.Additionally, the calibration parameters of the camera used were obtained. ULACs equipped with CDCs showed quality results and precision comparable to those obtained in surveys with photogrammetric cameras and UAV technology. This was validated as a low-cost, valuable tool for municipal authorities in small to medium-sized cities, where resources are often more limited than in larger cities.